Inhibition of ferredoxin: NADP+ reductase activity by the hexacyanochromate (III) ion. - Armstrong, F; Corbett, S (1986)
The small inorganic complex Cr(CN)6(3-) is a clean inhibitor of the ferredoxin: NADP+ reductase-catalysed oxidation of reduced spinach ferredoxin by NADP+. Independent spectrophotometric measurements show that millimolar additions of Cr(CN)6(3-) to mixtures of ferredoxin and ferredoxin NADP+ reductase give a marked attenuation of the difference spectrum characteristic of ferredoxin-ferredoxin: NADP+ reductase complex formation. Since there is no evidence, from NMR studies, for significant binding of Cr(CN)6(3-) to ferredoxin, these results indicate that Cr(CN)6(3-) binds to ferredoxin: NADP+ reductase at a site which is crucial to its interaction with the electron-transfer protein. The effective kinetic binding constant for Cr(CN)6(3-), measured at low ferredoxin concentration, is 445 M-1 (ie Kdiss congruent to 2 mM) at 25 degrees, pH7.5, I = 0.10 M. With assumption of a simple electrostatic interaction, an enzyme domain with an effective charge of 3+/4+ is proposed.